2009
DOI: 10.1021/jp8088098
|View full text |Cite
|
Sign up to set email alerts
|

Raman Characterization of a New Te-Rich Binary Compound: CdTe2

Abstract: Structural characterization by Raman spectroscopy of CdTe thin films electrodeposited in acidic conditions is considered in this work. This study focuses on the evolution of material properties as a function of the applied potential and the film thickness, demonstrating the possibility to obtain a new Te-rich compound with a II/VI ratio of 1/2 under specific bath conditions. Raman measurements carried out on etched samples first allow the elimination of the assumption of a mixture of phases CdTe + Te and tend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…4(a) shows the Raman spectrum of the CdTe before and after CdCl 2 treatment. The peak around 169 cm À 1 is assigned to the longitudinal-optical phonon (LO) of the CdTe [21][22][23]. The peak around 141 cm À 1 represents the mixture of the E phonon of the pure tellurium and the transverse optical phonon (TO) of the CdTe [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4(a) shows the Raman spectrum of the CdTe before and after CdCl 2 treatment. The peak around 169 cm À 1 is assigned to the longitudinal-optical phonon (LO) of the CdTe [21][22][23]. The peak around 141 cm À 1 represents the mixture of the E phonon of the pure tellurium and the transverse optical phonon (TO) of the CdTe [21].…”
Section: Resultsmentioning
confidence: 99%
“…The peak around 169 cm À 1 is assigned to the longitudinal-optical phonon (LO) of the CdTe [21][22][23]. The peak around 141 cm À 1 represents the mixture of the E phonon of the pure tellurium and the transverse optical phonon (TO) of the CdTe [21]. The peak around 123 cm À 1 is known to be the A 1 phonon of the pure tellurium phase [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical cathodic deposition of p-types can be enhanced under illumination. 3 -An additional complexity stems from the formation of multiple phases during the electrochemical deposition and growth, especially in the case of ternaries and higher multinaries (19,24,25). 4 -The chemical and electrochemical properties of non metals, such as S, Se, Te, are complex with several stable oxidation states, low solubility of electroactive species, usually hydroxyacids or oxides.…”
Section: General Characteristics Of Semiconductor Electrodepositionmentioning
confidence: 99%
“…For higher Te(IV) flux and at lower pH's and/or for more positive interfacial potential, a new metastable phase with a stoichiometry close to CdTe 2 is formed. It has a quasi amorphous structure and exhibits a reduced band gap close to 1.3 eV (21,22,25,30). , 19 (24) 1-10 (2009) CI(G)S. During the last decades, researches concerning I-III-VI 2 , such as CuInSe 2 or Cu(In,Ga)Se 2 , compounds have been widely developed (4,5,31).…”
Section: General Characteristics Of Semiconductor Electrodepositionmentioning
confidence: 99%
“…The deposition rate of the Terich amorphous CdTe is much higher than that of the crystalline CdTe. Lincot et al also reported the electro deposition of a Terich compound from the acidic bath [1,17,18]. If a crystallized CdTe film can be produced by annealing of the amorphous CdTe film, the time required for the preparation of the CdTe layers of the solar cells will be reduced significantly.…”
Section: Introductionmentioning
confidence: 99%